Femtosecond Laser Microfabrication of Porous Superwetting Materials for Oil/Water Separation: A Mini-Review - Feng, Na; Yong, Jiale (Frontiers in Chemistry, 2020)
Frequent oil-leakage accidents and large quantities of oil-bearing wastewater discharge cause severe environmental pollution and huge economic losses. Recently, superwetting porous materials are successfully utilized to separate oil/water mixture (OWM) based on the different interfacial behavior of water and oil. Here, we summarize the recent development of efficient oil/water separation (OWS) based on the femtosecond laser-induced superwetting materials. The typical wettability-based separation manners (including “oil-removing” and “water-removing”) and the characteristic of the femtosecond laser are introduced as background. Various laser-structured porous sheets with either superhydrophobicity or underwater superoleophobicity are successfully used to separate different OWMs. The laser processing methods, surface wettability, separation process, and separation mechanism of these laser-structured separation materials are reviewed. Finally, the current challenges and prospects in achieving OWS by femtosecond laser microfabrication are discussed.